2000
DOI: 10.1080/10473289.2000.10464031
|View full text |Cite
|
Sign up to set email alerts
|

Speciated Hydrocarbon Emissions from Small Utility Engines

Abstract: Partially speciated hydrocarbon (HC) emissions data from several small utility engines, as measured by a Fourier Transform Infrared analyzer, are presented. The engines considered have nominal horsepower ratings between 3.7 and 9.3 kW. Both side-valve and overhead-valve engines are studied, and four different fuels are used in the engines. The results indicate that the small HCs present in the exhaust tend to be in the form of either methane or unsaturated HCs. Other small alkanes, such as ethane and propane, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2001
2001
2002
2002

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…Student A began working on this project after helping with a study of the speciated hydrocarbon emissions from small utility engines operating under different fuels. 10 As an undergraduate student working on this project, he was primarily responsible for the coordination of our laboratory tests with field tests being organized by one of the industrial sponsors of the project. This led to the development of an in-laboratory test that mimicked the life cycle of the engines in actual field use.…”
Section: Results Of Research Projectmentioning
confidence: 99%
See 1 more Smart Citation
“…Student A began working on this project after helping with a study of the speciated hydrocarbon emissions from small utility engines operating under different fuels. 10 As an undergraduate student working on this project, he was primarily responsible for the coordination of our laboratory tests with field tests being organized by one of the industrial sponsors of the project. This led to the development of an in-laboratory test that mimicked the life cycle of the engines in actual field use.…”
Section: Results Of Research Projectmentioning
confidence: 99%
“…degree. Initially, his work as an undergraduate was in support of another small engines emissions project, the details of which can be found in Reisel, et al(2000) 10 Details of the procedures used in Phase 1 of this project can be found in Caceres, et al 11 Briefly, both side-valve and overhead-valve, air-cooled, sparkignition engines with a nominal power rating of 4.8 kW were tested over a total of 200 hours. The nominal lifetime of these engines is 125 hours, but similar engines have longer nominal lifetimes, and it is expected that most users will operate the engines longer than 125 hours.…”
Section: Description Of the Research Projectmentioning
confidence: 99%